2019
DOI: 10.1111/ele.13217
|View full text |Cite
|
Sign up to set email alerts
|

Functional trait trade‐off and species abundance: insights from a multi‐decadal study

Abstract: Phylogenetically informed trait comparisons across entire communities show promise in advancing community ecology. We use this approach to better understand the composition of a community of winter annual plants with multiple decades of monitoring and detailed morphological, phenological and physiological measurements. Previous research on this system revealed a physiological trade‐off among dominant species that accurately predicts population and community dynamics. Here we expanded our investigation to 51 sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 85 publications
(204 reference statements)
1
22
0
Order By: Relevance
“…Understanding seed banks has proven to be exceptionally challenging, rendering our knowledge of early life history traits incomplete across the plant kingdom [ 1 , 2 ]. Studies are needed to enumerate and predict changes in seed banks, particularly to ascertain if plant species’ or communities’ seed banks respond to environmental changes [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Studies of annual seed banks in deserts may be especially useful to study seed bank trait–environment interactions because these environments are characterized by extreme variability in temperature and precipitation [ 9 , 10 ]—variability that increasingly characterizes Earth’s environments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding seed banks has proven to be exceptionally challenging, rendering our knowledge of early life history traits incomplete across the plant kingdom [ 1 , 2 ]. Studies are needed to enumerate and predict changes in seed banks, particularly to ascertain if plant species’ or communities’ seed banks respond to environmental changes [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Studies of annual seed banks in deserts may be especially useful to study seed bank trait–environment interactions because these environments are characterized by extreme variability in temperature and precipitation [ 9 , 10 ]—variability that increasingly characterizes Earth’s environments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of seed banks of rare and common species in desert annual plant communities may aid an understanding of seed bank traits. For several reasons, desert annual plants are an established model system for seed bank studies: their aboveground life cycle stages are exceptionally fast, they are mostly surficial in the soil (≤2 cm depth), and their responses to changes in the environment often occur over short durations of time [ 8 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate changes have altered the physical environments (e.g., soil moisture, temperature, and water vapor pressure deficit) of plant communities and shifted community species composition due to the fact that different functional groups, plant genera, and species respond divergently to climate change [1][2][3][4][5]. Based on long-term monitoring forest plots, several recent studies reported that climate change, especially drought, induced community composition to be shifting towards more dry-tolerant individuals and genera in Central American forests [1,6], West African forests [7], Amazon forests [2,8], and some temperate forests [9].…”
Section: Introductionmentioning
confidence: 99%